Respuesta :
We first need dy/dx.
dy/dx = -2sin(x/2)(1/2)
dy/dx = -sin(x/2)
We now find d^2y/dx^2.
d^2y/dx^2 = -cos(x/2)(1/2)
d^2y/dx^2 = -(1/2)cos(x/2)
dy/dx = -2sin(x/2)(1/2)
dy/dx = -sin(x/2)
We now find d^2y/dx^2.
d^2y/dx^2 = -cos(x/2)(1/2)
d^2y/dx^2 = -(1/2)cos(x/2)
The value of 2nd derivative of y is,
[tex]\dfrac{d^2y}{dx^2}= -\dfrac{1}{2} cos(\dfrac{x}{2})[/tex]
Given :
[tex]y = 2cos(\dfrac{x}{2})[/tex] ---- (1)
Solution :
Differentiate equation (1) with respect to x we get,
[tex]\dfrac{dy}{dx}= -2sin(\dfrac{x}{2})\times \dfrac{1}{2}[/tex]
[tex]\dfrac{dy}{dx}= -sin(\dfrac{x}{2})[/tex] ----- (2)
Now differentiating equation (2) we get,
[tex]\dfrac{d^2y}{dx^2}= -cos(\dfrac{x}{2})\times \dfrac{1}{2}[/tex]
[tex]\dfrac{d^2y}{dx^2}= -\dfrac{1}{2} cos(\dfrac{x}{2})[/tex]
For more information, refer the link given below
https://brainly.com/question/14496325?referrer=searchResults